1988
DOI: 10.1007/bf01963064
|View full text |Cite
|
Sign up to set email alerts
|

Bacteraemia related to indwelling central venous catheters: Prevention, diagnosis and treatment

Abstract: Infective episodes in immunocompromised children with indwelling central venous catheters were studied prospectively for one year. Culture of catheter hubs and skin at catheter entry sites during the first six months suggested that hub contamination was important in the pathogenesis of catheter colonization. The incidence of catheter-related bacteraemia, and possible catheter-related bacteraemia, fell by 56.5% following alterations in the protocol for manipulative care of catheters, from 5.82 per 1000 catheter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
1
1

Year Published

1993
1993
2015
2015

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(35 citation statements)
references
References 14 publications
0
33
1
1
Order By: Relevance
“…By a quantitative pour plate method, Wing et al (1979) found blood taken via a central line associated with septicaemia gave 400x the number of organisms cultured from peripheral blood. In a larger study Weightman et al (1988) found at least a ten fold difference in catheter versus peripheral blood cultures in patients with bacteraemia.…”
Section: Blood Culture Methodsmentioning
confidence: 85%
“…By a quantitative pour plate method, Wing et al (1979) found blood taken via a central line associated with septicaemia gave 400x the number of organisms cultured from peripheral blood. In a larger study Weightman et al (1988) found at least a ten fold difference in catheter versus peripheral blood cultures in patients with bacteraemia.…”
Section: Blood Culture Methodsmentioning
confidence: 85%
“…Once catheter infection is decided the therapeutic approach will be affected by the severity and the type of infection, status of the patient and the necessity of the catheter and the type of the etiologic agent (7,8,9). The spectrum of microorganisms should be known to decide about the route of infection and to take preventive measures and to decide empirical antibioitic therapy.…”
Section: DI Is Sc Cu Us Ss Si Io On Nmentioning
confidence: 99%
“…(4) Local device-site care procedures, as addressed in the protocol, should be standardized as much as possible [7,11,12].…”
Section: Special Conditionsmentioning
confidence: 99%
“…The protocol should state clearly the point at which such a conversion may take place and the measures that are planned to ensure adequate absorption of an orally administered drug. The duration of therapy should be clearly defined in the protocol (usually, a minimum of 7-10 days) [2,11,13].…”
Section: G Administration Of the Study Drugmentioning
confidence: 99%